Collections of Memory Institutions: New Trends for Research - Pacevičius, Arvydas (Bibliotheca Lituana, 2012)
The publication features information on research done during the Bibliotheca Lituana project. In particular the focus is on collections of memory institutions, new perspectives on library and other memory institution, i.e. archives, museums, research. Modern library history has adopted relevant theoretical perspectives from social and cultural theory. Currently these perspectives incorporate not only the activities and collections of the aforementioned institutions but also the more widely interpreted information infrastructure, that do not have libraries as their main frame of reference. Problems faced publishing archival sources are also examined. It was determined that insufficient attention is given to research and publication of old catalogues, inventories and book listings. On the other hand a unified system and methodology for publishing of the aforementioned sources does not exist. We come to a conclusion that through new research paradigms, an interdisciplinary approach and change of thought in the archival, librarian and museology communities, we can start systematic research of libraries and other memory institutions. Their results would complement the pages of the continued Bibliotheca Lituana publications.
Keywords: none